PENDIDIKAN KARAKTER BERBASIS CERITA RAKYAT BERTEMA BATU BELAH SEBAGAI PEMBENTUKAN KARAKTER SISWA - Malawat, Insum (JURNAL TRITON PENDIDIKAN, 2017)
Character education is the capital to maintain the integrity of the nation as a multicultural country. Character education aims to develop the noble values of Pancasila, namely the development of potential learners to become human noble and have nationalism and patriotism. Character education does not just teach what is right and what is wrong. More than that, character education is an effort to instill good habituation (habituation) so that learners are able to behave and act on the values that have become personality. In other words, a good character education must involve good knowledge (moral knowing), good feelings or loving good (moral feeling) and good behavior (moral action) to form the embodiment of unity of behavior and attitude of life of learners. Implimentation of character education in schools should be tailored to the noble values of the nation, one of which is contained in various stories of the people of the archipelago. Folklore is the largest field of character education. Potential folklore archipelago that spans from Sabang-Merauke can be analyzed macro based on the theme. This paper focuses on the study of folklore on the theme of stone, the story that uses stone media as the final consequence of dishonest behavior through pragmatic approach.